Elucidation of Lactoferrin and Lactoperoxidase in Separation Technique: Elucidation of Lactoferrin and Lactoperoxidase in Separation Technique - Mukhopadhyay, Goutam (International Journal of Pharmaceutical & Biological Archive, 2018)
This review confers the biological properties of the glycoproteins lactoferrin (Lf) and lactoperoxidase (Lp). Lf is an iron-binding protein present in huge amounts in colostrum and breast milk, in external secretions, and polymorphonuclear leukocytes. Lp is a member of a large group of mammalian heme peroxidases that originates in exocrine secretions including milk. Lf holds numerous biological functions that contain roles in iron metabolism, cell proliferation, and differentiation, antibacterial, antiviral, and antiparasitic activity. Lp is accountable for the inactivation of an extensive range of microorganisms and hence significant in the defense mechanism in human secretions such as saliva, tear fluid, and milk. Lately discovered is the anticancer activity. Extraction of Lf and Lp can be done from raw milk by cation exchange chromatography. Separation and purification technologies can be achieved from whey and bovine milk by batch extraction, chromatographic techniques, and with hydrophobic ionic liquids. Polyclonal antibodies were made to purified breast milk Lf and used in an ELISA to estimate plasma concentrations in investigations of innumerable aspects of the inflammatory reaction. The usage of Lp system in the dairy industry and the possible applications of the Lp system in further food systems and commercial products are emphasized here. Milk Lf is used as a dietary constituent that endorses growth of gastrointestinal tract of human infants and newborn nonhuman animals instantaneously on birth. The paper as well highlights the investigation breach and promising forthcoming research directions that require consideration.